Child Sexual Abuse: The Emerging Crime at our Doorsteps and the Role of Disclosure in Prevention - Jane , Kariuki, N.; Cecilia , Seba, N.; James , Mbugua,. K (African Journal of Education,Science and Technology (AJEST), 2015)
To report or not to report child sexual abuse remains a dilemma to many survivors with many opting to keep quiet about it. Self disclosure of sexual abuse is a critical component in initiating intervention to halt the abuse, address its immediate effects and decrease the likelihood of negative long term effects. Paine and Hansen (2002). Many incidences of child sexual abuse go unreported while the few that are reported never reach prosecution stage. Though Sexual abuse affects both children and adults, one would be tempted to think that adults are more likely to disclose sexual abuse compared to children. This however is not the case. Literature shows the rate of disclosure is equally low in both children and adult. This paper is based on documented studies on child sexual abuse and examines how disclosure can be utilized as a tool in prevention of child sexual abuse laying emphasis on the process of disclosure and the role of the various parties such as parents and professionals working with the survivors of abuse. The paper also highlights some of the reasons why survivors of child sexual abuse fail to disclose and factors that can be considered in enhancing disclosure. Findings from reviewed literature indicates that the highest number of child sexual offences is committed by people close to the survivor such as parents, siblings, uncles, other close relatives, neighbors and domestic workers. Disclosing offences inflicted by people so close yet so distance in as far as respect for relationship and or responsibility towards the minors still remains a challenge, a challenge as big as disclosing the sexual abuse itself.